Confocal imaging of organic anion transport in intact rat choroid plexus - Breen, Christopher; Fricker, Gert (American journal of physiology. Renal physiology, 2002)
We used confocal microscopy and quantitative image analysis to follow the movement of the fluorescent organic anion fluorescein (FL) from bath to cell and cell to blood vessel in intact rat lateral choroid plexus. FL accumulation in epithelial cells and underlying vessels was rapid, concentrative, and reduced by other organic anions. At steady state, cell fluorescence exceeded bath fluorescence by a factor of 3-5, and vessel fluorescence exceeded cell fluorescence by a factor of ∼2. In cells, FL distributed between diffuse and punctate compartments. Cell and vessel accumulation of FL decreased when metabolism was inhibited by KCN, when bath Na+ was reduced from 130 to 26 mM, and when the Na+ gradient was collapsed with ouabain. Cell and vessel accumulation increased by >50% when 1-10 μM glutarate was added to the bath. Finally, transport of FL and carboxyfluorescein (generated intracellularly from carboxyfluorescein diacetate) from cell to blood vessel was greatly diminished when medium K+ concentration ([K+]) was increased 10-fold. These results 1) validate a new approach to the study of choroid plexus function, and 2) indicate a two-step mechanism for transepithelial organic anion transport: indirect coupling of uptake to Na+ at the apical membrane and electrical potential-driven efflux at the basolateral membrane.
Gesehen am 25.04.2017